Americae Sive Novi Orbis Nova Descriptio - Ortelius, Abraham, 1527-1598. (North Carolina Department of Cultural Resources, 1587)
Colored print. Decorative illustrations surrounding title. Shows North America, South America, Papua New Guinea, and Antarctica. Includes rivers, mountain ranges, and Native American settlements. Latin text on verso: "Novus Orbis." This map was first produced by Abraham Ortelius, a rare book dealer, in 1564. It reflects Jacques Cartier's discoveries between the years 1534 and 1541 and shows the St. Lawrence River as the gateway to the Pacific. This map appears in Ortelius' Atlas, Theatrum Orbis Terrarum with maps engraved by Franz Hogenberg. There were three different copperplate engravings of this map in the years 1570, 1579, and 1587. This print is from the 1587 plate. This map was previously classified as 33 MAP-0-3